APLIKASI PENGOLAHAN DATA ALAT DAN BAHAN KIMIA LABORATORIUM KIMIA SEKOLAH TINGGI TEKNOLOGI INDUSTRI BONTANG - Masagus Muhammad Yusuf; Irianto Irianto; Syahri Djalil (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2019)
Processing data on tools and chemicals in chemical laboratories is a crucial problem because it is part of the management and utilization of laboratories effectively and efficiently and is also right on target. However, it was realized that many problems were faced, especially laboratory officers in managing data on tools and chemicals, one of which was a system of data collection of tools and chemicals that had not yet used integrated information system applications. The management of data on tools and chemicals is still manual, which results in the inventory data of items being late known. Another problem that arises is that ordering goods cannot be done quickly because there are stages that must be done until the item is received. as well as the process of procuring equipment and chemicals also require time until the goods received by the laboratory management are also part of the problem at hand. To overcome the above problems, a computerized system is needed that is able to work more effectively, efficiently and thoroughly, so that the process of collecting tools and chemicals is better than the previous one. This research was conducted to meet the needs of an information system for data collection of tools and chemicals in the laboratory